Financial Ratio Analysis of PT Bank Central Asia Tbk Period 2019 – 2022 - Yeni, Wa Ode Sri; Kristanti, Yosephine; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
The banking sector is a vital sector for the development of a country. To find out the company's performance, an analysis of the company's financial reports can be carried out, and the increases and decreases that occur can be used as an analysis for the company's future. The research results on the financial statements of PT Bank Central Asia Tbk for the 2019–2022 period show that total current assets will be higher than total short-term liabilities, so the quick ratio presentation will decrease. From a liquidity perspective, a bank's health is measured by its loan-to-deposit ratio. The solvency ratio shows that the company's results have increased yearly because the level of assets owned by the company is relatively high, and the initial capital tends to be small. This can result in the company's level of capital health being sufficient. The profitability ratio results show that the company gets high ROE and ROA results, so it can be interpreted that the net gain is relatively high.